2021
DOI: 10.1080/10942912.2021.1977655
|View full text |Cite
|
Sign up to set email alerts
|

Application of curcumine and its derivatives in the treatment of cardiovascular diseases: a review

Abstract: Cardiovascular diseases are the leading cause of death in the world and scientists pay a lot of attention to identify and reveal the mechanisms of their occurrence. Recently, the attention of scientists is focused increasingly on plant derivatives, such as flavonoids and polyphenols, due to their specific biological effects. One of these compounds is curcumin, which has many biological properties. Numerous studies have been performed to understand the molecular basis of the therapeutic properties of curcumin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Can scavenge reactive oxidizing substances [180] Enhances the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [116] Activates antioxidant factors including Nrf2, heme oxygenase (HO-1), and proliferator-activated receptor-gamma coactivator (PGC-1α) [181] Prevents LDL (low-density lipoprotein) oxidation [182] Table 2. Cont.…”
Section: Antioxidantmentioning
confidence: 99%
“…Can scavenge reactive oxidizing substances [180] Enhances the activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) [116] Activates antioxidant factors including Nrf2, heme oxygenase (HO-1), and proliferator-activated receptor-gamma coactivator (PGC-1α) [181] Prevents LDL (low-density lipoprotein) oxidation [182] Table 2. Cont.…”
Section: Antioxidantmentioning
confidence: 99%
“…As a member of the mitogen-activated protein kinase family, JNK2 influences multiple cellular stress responses, including inflammatory responses, oxidative stress, cell death, cell survival, and protein expression, in various tissues of diabetic animals (Liu et al 2014 ; Zhou et al 2016 ; Jiao et al 2015 ; Fan et al 2012 ). JNK was found to be inhibited by curcumin, which is a potent protector against cardiovascular disease (Fiorillo et al 2008 ; Stamenkovska et al 2021 ; Pan et al 2013 ) found that C66 has a high affinity for JNK2 binding, which potentiates its anti-inflammatory effects. In addition, Li et al ( 2018a , b , c ) have found that JNK2 deletion is associated with reduced aortic inflammation, oxidative stress, apoptosis, and fibrosis, caused by diabetes, but significant changes in the aorta of diabetic JNK2 −/− mice were not reported after C66 treatment.…”
Section: C66 and Diabetes-associated Complicationsmentioning
confidence: 99%
“…More specifically, they found that CUR administration for six weeks improved the vascular response to Ach in diabetic rats with streptozotocin-induced endothelial dysfunction and that this effect was linked to reduced O 2 − generation in the mesenteric arteries. Additionally, different CUR analogs protect the heart from ischemic damage and improve cardiac function by strengthening the antioxidant defense mechanisms [14][15][16][17]. According to Nakmareong et al [11], the potential of CUR and THC to enhance the hemodynamic condition and restore aortic responsiveness is linked to the restoration of eNOS expression and blood plasma nitrate/nitrite levels.…”
Section: Cur-and Thc-related Vascular Protection In L-name-induced Hy...mentioning
confidence: 99%